A sociological analysis of constructing a hero in social interactions as the social malingering: A case study of “A Hero” Movie - A. Isa Maleki; S.S. Beheshti (Taḥqīqāt-i Farhangī-i Īrān, 2023)
This article aims to discover and divulge the hidden and obvious themes of social malingering in the actions of characters in the movie A Hero, by Asghar Farhadi. Since, according to some critics and thinkers, the content and themes of Iranian cinema have a deep connection with social issues and events, this study is an attempt to highlight social interactions and analyze everyday life in contemporary Iran. The research was conducted using a qualitative method and content analysis technique. The main problems discussed here were: Why do we construct a hero? What is the relationship between the phenomena of social malingering and constructing a hero in everyday life? Findings show the phenomenon such as social malingering and a hero construct in everyday life, in the mutual relationship and dialectic of attempt and failure, the inefficiency of social and political institutions, individuality cult, ideological morality, ontological insecurity and the reduction of social capital among others. It seems the social malingering and constructing a hero may be strategies for survival, especially the survival of honor and social acceptability in interactions and everyday life, the last type of social action and initiative to protect oneself and society.